Predicting Potential Climatic Suitability for Ditylenchus dipsaci in India Using MaxEnt Modelling (Indian Journal of Nematology, 2025)
The stem and bulb nematode, Ditylenchus dipsaci is a major nematode parasite of plants that causes economic damage to a wide range of plants, particularly in areas with a temperate climate. According to the Plant Quarantine Order (Regulation of Import into India) 2003, this nematode is classified as a quarantine pest and is not known to occur in India. Assessing the suitable habitat and possible geographic distribution areas for D. dipsaci would help us to better understand its level of establishment and spread in India. Therefore, in this work, the maximum entropy (MaxEnt) model was employed to determine the possible geographic distribution in India under the current climate. The model-predicted suitable areas for D. dipsaci are distributed in the parts of Himachal Pradesh and Uttarakhand states, and the Jammu and Kashmir union territory in northern India, besides Sikkim, Arunachal Pradesh and a few parts of Manipur in the northeastern region. Among the bioclimatic variables, annual mean temperature (Bio1) and precipitation seasonality (Bio15) have more influence on the geographic suitability of D. dipsaci.